Lacrimal syringing versus combined lacrimal probing and syringing for treatment of congenital nasolacrimal duct obstruction in children - Apoorv Bhardwaj; Karamjit Singh; Karan Sharma; Dharamvir Chalia; Sat Pal (International Journal of Medical Research and Review, 2016)
Introduction: Congenital nasolacrimal duct obstruction (CNLDO) is the most common abnormality of the lacrimal system in the early years of life.Aims and Objectives: To rationalize the applicability of lacrimal syringing alone in comparison to combined lacrimal probing and syringing for the treatment of congenital nasolacrimal duct obstruction in children.Material and Methods: The study was conducted on fifty patients suffering from congenital nasolacrimal duct obstruction randomly selected from the outpatient department of Regional Institute of Ophthalmology, Government Medical College, Amritsar.Results: Majority of cases could be cured by single attempt of combined probing and syringing and cure rate could be enhanced by repeated attempts within 1st two years of life.Conclusion: The overall assessment of the study indicates that although the success rate of gentle lacrimal syringing alone is low yet it is worthwhile to try this least traumatic procedure in each and every child reporting with congenital nasolacrimal duct obstruction under 1 year of age. If lacrimal syringing as a first hand procedure fails, then lacrimal probing along with syringing should preferentially be attempted and may be repeated 2-3 times at a minimum interval of 2 weeks each till the patency of nasolacrimal duct is restored.